Diary of an awesome friendly kid eaudiobook Rowley jefferson's journal. - Kinney, Jeff (Diary of an Awesome Friendly Kid, 2019)
Get ready for a whole new look into Jeff Kinney's Diary of a Wimpy Kid! Introducing the newest Wimpy Kid author-Rowley Jefferson! Rowley's best friend Greg Heffley has been chronicling his middle-school years in thirteen Diary of a Wimpy Kid journals . . . and counting. But it's finally time for readers to hear directly from Rowley in a journal of his own. In Diary of an Awesome Friendly Kid, Rowley writes about his experiences and agrees to play the role of biographer for Greg along the way. (After all, one day Greg will be rich and famous, and everyone will want to know his life's story.) But Rowley is a poor choice for the job, and his "biography" of Greg is a hilarious mess. Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal offers readers a new way to look at the Wimpy world-one fans won't want to miss!